2003
DOI: 10.1104/pp.103.034223
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Adenylyl Cyclase Controls Phototaxis in the Flagellate Euglena gracilis

Abstract: Euglena gracilis, a unicellular freshwater protist exhibits different photomovement responses, such as phototaxis (oriented movement toward or away from the light source) and photophobic (abrupt turn in response to a rapid increase [step-up] or decrease [step-down] in the light fluence rate) responses. Photoactivated adenylyl cyclase (PAC) has been isolated from whole-cell preparations and identified by RNA interference (RNAi) to be the photoreceptor for step-up photophobic responses but not for step-down ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 21 publications
0
68
1
Order By: Relevance
“…Optical activation of intracellular signaling via modified opsins (Kim et al, 2005) and blue-light-activated adenylate cyclases (PACs) from the flagellate Euglena gracilis (Iseki et al, 2002;Ntefidou et al, 2003) can trigger rapid and reversible increases in cAMP levels in vitro and modulate behavior in Drosophila in vivo (Schroder-Lang et al, 2007). Phototropins, photo-regulated protein kinases (Huala et al, 1997;Briggs et al, 2001), might also provide useful tools for biochemistry studies of phosphorylation events within a cell that could complement ChR2/NpHR modulation of biochemical signaling, along with other lightactivated compounds yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Optical activation of intracellular signaling via modified opsins (Kim et al, 2005) and blue-light-activated adenylate cyclases (PACs) from the flagellate Euglena gracilis (Iseki et al, 2002;Ntefidou et al, 2003) can trigger rapid and reversible increases in cAMP levels in vitro and modulate behavior in Drosophila in vivo (Schroder-Lang et al, 2007). Phototropins, photo-regulated protein kinases (Huala et al, 1997;Briggs et al, 2001), might also provide useful tools for biochemistry studies of phosphorylation events within a cell that could complement ChR2/NpHR modulation of biochemical signaling, along with other lightactivated compounds yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 2003, Ntefidou et al reported that PAC itself or a molecule that is similar to PAC was also involved in positive and negative phototaxis. 4 PAC consists of alpha and beta subunits both having two flavin binding domains F1 and F2, each followed by a catalytic domain of adenylyl cyclase C1 and C2, respectively. The flavin binding domains of PAC are similar to the N-terminal region of the flavoprotein AppA from the purple bacterium Rhodobacter sphaeroides.…”
Section: Introductionmentioning
confidence: 99%
“…The motion is not purely phototactic: Euglena cells in dark conditions perform random motion with much spinning [38]. The threshold intensity of blue light required to cause the negative phototaxis is approximately 10 mW/cm 2 [39]. This is an almost two times lower limiting light intensity than that for a normal daylight [40].…”
Section: Systemmentioning
confidence: 96%
“…Although we successfully described the population statistics, on the single cell level the mechanism of the active fluctuations and of the observed "fatigue" remains unclear. This mechanism can be investigated further if one addresses complex and not fully understood impulse-response behaviors involving the photoactivated adenylyl cyclase [39,50] and protein kinase [51].…”
Section: Discussionmentioning
confidence: 99%